Humanitarian erudition in the professional competence of the culturologist - Гриценко, Валентина Степанівна (Київський національний університет імені Тараса Шевченка, 2018)
The article is devoted to the study of humanitarian education as a sign of the professionalism of a culturologist. Special attention is paid to the actualization of cultural science as a science capable of influencing the contemporary processes of cultural development, the necessity of taking into account the given factor in the formation of culturological competences. Humanitarian “all-seeing” of cultural studies is considered as the basis to be the dominant of modern humanities. In the conditions of crisis of self-definition a requirement grows in development of knowledge about a culture, a too – in humanitarian erudition as condition of culturological vision of all. She can be formed due to corresponding protocols of professional preparation of culturologist, procedures of grant to them the necessary knowledge and practical skills, in fact universality of the expected competenses must be commensurable to the calls of modern humanitarian sciences in their essence understanding. It does actual a question in relation to the value of humanitarian knowledge on the modern stage of development of Man, but culturology, busy at first of all the analysis of spiritual senses, finds out her unique productivity among humanitarian research projects. Her humanitarian dominant finds all more confirmations in a scientific environment that promotes demand on professional accordance to such her position, that in turn envisages going beyond the scopes of formal set of competenses. Humanitarian erudition eliminates any formalization, in fact all-round form, is charged energy of human development, inflexible in aspiration to the spiritual kernel of culture. Working mainly with empiric facts, real culturologist is at essence level of their understanding, owning wide knowledge about procedures of examinations of the cultural phenomena, criteria of their estimation. A humanitarian awareness allows to hin to be included in the thin sphere of internal man from positions of knowledge of human psyche, typology of the emotional states, methods of questioning, questionnaire, testing, analytical procedures. Among the terms of competence an important place belongs to understanding of heuristic potential of analysis of the art straight related to the essence human kernel in all many-sided nature of his display.

Стаття присвячена дослідженню гуманітарної освіченості як ознаки фаховості культуролога. Окрему увагу приділено актуалізації культурології як науки, здатної впливати на сучасні процеси розвитку культури, розглянуто необхідність врахування даного фактора у формуванні культурологічних компетенцій. Гуманітарне "всебачення" культурології розглянуто як підстава бути домінантом сучасної гуманітаристики.
Гуманітарна ерудиція у фахових компетенціях культуролога
Keywords: гуманітаристика; ерудиція; гуманітарний домінант; культура; сутність людини; сутнісна універсальність; фахові компетенції; humanitarism; erudition; humanitarian dominant; culture; the essence of man; essential universality of man; professional competencies